Excessive use of social networking sites and financial well-being among young adults: the mediating role of online compulsive buying. Issue 2 (20th May 2021) - She, Long; Rasiah, Ratneswary; Waheed, Hassam; Pahlevan Sharif, Saeed
Abstract : Purpose: This study aims to examine the mediating role of online compulsive buying in the association between excessive use of social networking sites (SNS) and financial well-being among Chinese young adults. Design/methodology/approach: A sample of 539 SNS users and active online shoppers (M age = 20.32 years, SD age = 2.11) completed an online survey questionnaire measure of excessive use of SNS, online compulsive buying and financial well-being. Covariance based-structural equation modelling was used to assess the measurement model and the proposed mediation model. Findings: Results indicated that excessive use of SNS was positively related to online compulsive buying behaviour and financial anxiety. Also, the results showed that online compulsive buying mediated the positive relationship between excessive use of SNS and financial anxiety. Practical implications: Several implications were suggested and discussed to enhance the levels of financial well-being among youths by tackling their problematic behaviour such as excessive SNS usage and online compulsive buying. Originality/value: The findings of this study contribute to the limited body of knowledge in the area of financial well-being and further improves our understanding of the effect of the excessive use of SNS on financial well-being and the mechanism behind it.